Спрямованість фізичного виховання учнів середнього шкільного віку - Климчук, Інна; Пантік, Василь; Klimchuk, Inna; Pantik, Vasiliy (Східноєвропейський національний університет імені Лесі Українки, 2013)
У зв’язку із соціально-економічною перебудовою суспільства, незадовільними умовами життя великої частини населення, екологічного несприятливого стану навколишнього середовища значно знижені компенсаторно-пристосувальні можливості дитячого організму та його опірності до дії різних шкідливих факторів. На особливу увагу в наш час заслуговують діти шкільного віку, стан здоров’я яких значно погіршується протягом шкільного навчання. As a result of socio-economic society revolution, unsatisfied conditions of living of the biggest part of population, ecological unfa¬vourable conditions of environment are dramatically lowered the compensatory-adaptive abilities of child’s organism and its resistance to different harmful factors. Attention is paid to children of school age whose health condition lowers during studying at school. Analysis of scientific and methodological literature lets us com to a conclusion that according to level of adaptation to educational activity at school, physical preparation and health condition pupils of middle school age have considerable differences and this needs applying of special health-improving measures. We are observing worsening of health condition, lowering of indices of physical preparation and functional abilities, and some psychological disorders, lowering of workability, violation of regime by children, chronic diseases.
Physical Education Orientation of Pupils of Middle School Age
Keywords: школярі; фізичне здоров’я; адаптація; функціональна система; захворюваність; психічна напруга; pupils; physical health; adaptation; functional system; sickness rate; psychological tension